The Community Service on Maintaining Cleanliness in RW 08 Labuhbaru Timur-Pekanbaru, Indonesia - Zaini, Abdul Kudus; Muttaqin, Muhammad Zaenal; Kumalasari, Cyintia (Teumulong: Journal of Community Service, 2023)
Labuhbaru Timur district has enormous potential to be developed, especially if the government provides some programs that support together with universities and communities. Labuh Baru Timur village has a demographic and topographic location that really supports daily activities and activities, provision of hospitality facilities, public awareness, especially visitors to Labuh Baru Timur village, regarding the importance of maintaining environmental cleanliness is still very lacking because there still people who throw rubbish carelessly, especially plastic waste. former packaging, drainage is congested, and the surrounding roads are damaged, and have holes, caused by vehicles exceeding the capacity of vehicles passing around Jalan Arjuna. The importance of understanding the Tri Hita Karana concept for the community from an early age so that environmental cleanliness can be enjoyed by all communities and public benefits can be achieved through socialization. and social action for environmental cleanliness. The basic essence of environmental management and preservation is the main capital for developing natural resources and human resources so an active role from the community is needed to maintain environmental sustainability.